Empowering Women Through Entrepreneurial Education : A SWOC Perspective Through the Lens of Gen Z - Pooja (AMC Indian Journal of Entrepreneurship, 2025)
Purpose : Within the policy framework of Viksit Bharat @2047, the primary focus is on women's empowerment to achieve socio-economic progress. As empowerment gains importance, women's entrepreneurship has become a pivotal driver of development. In the current context, Generation Z (Gen Z) recognizes the role of such education in fostering economic independence, a progressive mindset, and innovation among women. This study examines the perspectives of Gen Z female students on women’s empowerment through entrepreneurial education in India, and explores the strengths, weaknesses, opportunities, and challenges (SWOC) factors influencing this perspective. Methodology : A descriptive research design with an analytical approach was adopted, using primary data collected via a structured online questionnaire from 121 valid responses by Gen Z female students in Indian higher education institutions (HEIs), supplemented by secondary sources. Data were analyzed using descriptive statistics, frequency tables, percentage analysis, and simple ranking techniques. Findings : It is revealed in the findings that Gen Z female students in Indian HEIs viewed entrepreneurial education as a dynamic driver of women’s empowerment, appreciating mentorship, practical exposure, policy support, and inclusive learning environments. They emphasized the need for institutional, governmental, and industry collaboration to enhance skills, confidence, and opportunities for women entrepreneurs. Implications : The study highlighted practical implications for fostering women’s empowerment through entrepreneurial education, including mentorship programs, alignment with government initiatives, gender equality campaigns, industry–academia partnerships, and cross-disciplinary collaborations to equip Gen Z women in HEIs with skills, exposure, and opportunities for entrepreneurial success. Originality : Unlike prior research on women entrepreneurship and education, the current work built a new mode to examine and evaluate perceptions of female students of HEIs, especially Gen Z, in the commerce and management stream. The work could provide the basis for industry and academic collaboration to facilitate students’ learning and development of entrepreneurial skills in this field.